2005
DOI: 10.1073/pnas.0502352102
|View full text |Cite
|
Sign up to set email alerts
|

Human thiopurine S -methyltransferase pharmacogenetics: Variant allozyme misfolding and aggresome formation

Abstract: Thiopurine S-methyltransferase (TPMT) catalyzes the S-methylation of thiopurine drugs. TPMT genetic polymorphisms represent a striking example of the potential clinical value of pharmacogenetics. Subjects homozygous for TPMT*3A, the most common variant allele for low activity, an allele that encodes a protein with two changes in amino acid sequence, are at greatly increased risk for life-threatening toxicity when treated with standard doses of thiopurines. These subjects have virtually undetectable levels of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
105
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 38 publications
(63 reference statements)
14
105
0
Order By: Relevance
“…Destabilization due to disruption of the D151 hydrogen bonding network probably causes the quality control functions of the cell to target the variant protein for degradation. Other destabilized TPMT variants have been shown to be susceptible to proteosomal degradation which reduces the cellular levels of these proteins [34,35,36]. Therefore, the conflicting results regarding enzyme activity and protein levels reported by Salavaggione et al [62] and Ujjie et al [63] can likely be explained by the reduced intrinsic stability of this variant, since both measured parameters depend on the extent of cellular clearance in response to decreased protein stability.…”
Section: Biophysical Characterization Of Variantsmentioning
confidence: 50%
See 1 more Smart Citation
“…Destabilization due to disruption of the D151 hydrogen bonding network probably causes the quality control functions of the cell to target the variant protein for degradation. Other destabilized TPMT variants have been shown to be susceptible to proteosomal degradation which reduces the cellular levels of these proteins [34,35,36]. Therefore, the conflicting results regarding enzyme activity and protein levels reported by Salavaggione et al [62] and Ujjie et al [63] can likely be explained by the reduced intrinsic stability of this variant, since both measured parameters depend on the extent of cellular clearance in response to decreased protein stability.…”
Section: Biophysical Characterization Of Variantsmentioning
confidence: 50%
“…Most of the known protein variants exhibit decreased in vivo enzyme activity towards thiopurine substrates, but the molecular causes of reduced functionality have only been investigated for a handful of protein variants (to date), namely TPMT*2 (A80P) [33], TPMT*3A (A154T/Y240C) [34,35], TPMT*3B (A154T) [34,35], TPMT*3C (Y240C) [34,35], TPMT*5 (L49S) [33], TPMT*16 (R163H) [30], TPMT*21 (L69V) [29], TPMT*24 (Q179S) [29], TPMT*25 (C212R) [29], Introduction and TPMT*31 (I204T) [31]. The variant proteins are often found to be destabilized (due to amino acid substitution), making them susceptible to proteolytic degradation by the quality control system of the cell [34,35,36], although one exception is TPMT*5, which exhibits nearly complete loss of function rather than reduced structural stability [33].…”
Section: Influencing Activity -Molecular Causesmentioning
confidence: 99%
“…Genetic polymorphism in this enzyme has been reported and the variant enzyme was shown to misfold and subsequently form aggresome. 23 It has been reported that the TPMT genotype has a substantial impact on the mercaptopurine treatment response. 24 Previous studies also have shown that patients with homozygous mutant TPMT alleles exhibit very low enzyme activity and develop a severe hematopoietic toxicity after treatment with standard doses of thiopurines.…”
Section: Cancer Drugsmentioning
confidence: 99%
“…While many variant alleles of TPMT have been identified, three account for more than 95% of inherited TPMT deficiency: TPMT*2 (238G>C), TPMT*3A (460G>A, 719A>G) and TPMT*3C (719A>G) (Krynetski & Evans, 2003). It was demonstrated that specific TPMT variants have low activity due to aggregation of variant proteins, providing a structural explanation for the observed differences in TPMT activity (Wang et al, 2005). The patients with very low or undetectable TPMT activity are at high risk of severe, potentially fatal hematopoietic toxicity when they are treated with standard doses of thiopurines (Evans et al, 1991).…”
Section: Polymorphism Of Thiopurine-s-methyltransferase 6-mp Toxicitymentioning
confidence: 99%